Dose-dependent stimulation of human follicular steroidogenesis by a novel rhCG during ovarian stimulation with fixed rFSH dosing - Bøtkjær, Jane Alrø; Kristensen, Stine Gry; Olesen, Hanna Ørnes; Larsson, Per; Mannaerts, Bernadette; Andersen, Claus Yding (Frontiers in Endocrinology, 2022)
Background: Choriogonadotropin (CG) beta (FE 999302), a novel recombinant human (h)CG produced by a human cell line, has a longer half-life and higher potency than CG alfa produced by a Chinese hamster ovary cell line. hCG augments steroid production, but the extent of which CG beta treatment during ovarian stimulation (OS) increases steroidogenesis is unknown. Objective: To explore how increasing doses of CG beta during OS augment follicular steroidogenesis and change gene expression in cumulus cells. Study design: This study is part of a randomized, double-blind, placebo-controlled trial to investigate the efficacy and safety of CG beta plus recombinant follicle-stimulating hormone (rFSH) in women undergoing OS during a long gonadotrophin-releasing hormone agonist protocol. The study primary endpoint was intrafollicular steroid concentrations after CG beta administration. Secondary outcomes were gene expression of FSHR, LHR, CYP19a1, and androgen receptor (AR). Participants/methods: 619 women with anti-Müllerian hormone levels 5–35 pmol/L were randomized to receive placebo or 1, 2, 4, 8, or 12 µg/day CG beta from Day 1 of OS plus rFSH. Follicular fluid (FF) (n=558), granulosa (n=498) and cumulus cells (n=368) were collected at oocyte retrieval. Steroid FF hormones were measured using enzyme-linked immunosorbent assays, gene expression was analyzed in cumulus cells by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) and single nucleotide polymorphism (SNP) analysis was performed in granulosa cells. Results: 17-OH-progesterone, androstenedione, testosterone, and estradiol concentrations significantly increased in a CG-beta dose-dependent manner during OS (p<0.0001), reaching up to 10 times higher values in the highest dose group versus placebo. There was no difference between CG beta dose groups and placebo for progesterone. Expression levels of CYP19a1 increased significantly in the highest dose group of CG beta (p=0.0325) but levels of FSHR, LHR and AR were not affected by CG beta administration. There were no differences between the FSHR(307) or LHR(312) SNP genotypes for dose-dependent effects of CG beta in relation to number of oocytes, intrafollicular steroid hormone levels, or gene expression levels. Conclusions: These results reflect the importance of the combined effect of FSH and hCG/LH during OS on granulosa cell activity, follicle health and potentially oocyte quality.